2021
DOI: 10.1088/1742-6596/1918/4/042085
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical creative thinking ability of students in treffinger and brain-based learning at junior high school

Abstract: The purpose of this experiment was to comprehensively examine whether innovative Brain-Based Learning and Treffinger learning was effective for developing mathematical creative thinking ability at junior high school. The research design was a quasi-experimental non-equivalent control-group design. The population was all grade VIII students at Junior High School in the 2019/2020 school year. The samples were two classes determined by a randomized class. Data collection techniques with tests. Data analysis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…For example, in Jordan At-Taraweh et al (2021) use of such an approach improved students' achievement in mathematics. This finding was repeated in Indonesia and other countries (Wijayanti et al, 2021;Riskiningtyas & Wangid, 2019;Priatna, 2017;Kartikaningtyas, V., Kusmayadi, T.A., & Riyadi, R., 2018;Noureen, G., Awan, R. N., & Fatima, H., 2017;Mastoni, E., Sumantri, M. S., & Ibrahim, N., 2019). This situation is similar to studies on the effectiveness of brain-based learning in physics; Saleh and Subramaniam (2019), Saleh (2012aSaleh ( , 2012bSaleh ( , 2012c and Sani et al (2019a) all found a positive effect of using BBL to improve students' performance in the subject.…”
Section: Paper | 75supporting
confidence: 82%
See 2 more Smart Citations
“…For example, in Jordan At-Taraweh et al (2021) use of such an approach improved students' achievement in mathematics. This finding was repeated in Indonesia and other countries (Wijayanti et al, 2021;Riskiningtyas & Wangid, 2019;Priatna, 2017;Kartikaningtyas, V., Kusmayadi, T.A., & Riyadi, R., 2018;Noureen, G., Awan, R. N., & Fatima, H., 2017;Mastoni, E., Sumantri, M. S., & Ibrahim, N., 2019). This situation is similar to studies on the effectiveness of brain-based learning in physics; Saleh and Subramaniam (2019), Saleh (2012aSaleh ( , 2012bSaleh ( , 2012c and Sani et al (2019a) all found a positive effect of using BBL to improve students' performance in the subject.…”
Section: Paper | 75supporting
confidence: 82%
“…This was followed by the integration of BBL in secondary schools, which accounted for 16% of the studies. These include those by Al-Tarawneh et al (2021), Alanazi (2020) and Wijayanti et al (2021). 12% of the studies conducted on the integration of BBL in science classrooms focused on form school students (3 studies), namely those of Saleh (2012a;2012b;2012c), while only 8% of the studies were conducted on primary schools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that these constructs relies on brain-based theory principles for their integration in the classroom. Some of these construct include brain-based learning (Al-Tarawneh et al, 2021;Alanazi, 2020;Al-Balushi & Al-Balushi, 2018;Riskiningtyas & Wangid, 2019;Sani et al, 2019;Wijayanti, Khasanah, Rizkiana, Mashuri, Dewi & Budhiati, 2021), brain-based learning approach (Akyürek & Afacan, 2013) brain-based teaching (BBT) (Saleh, 2012a;Saleh, 2012b), brain-based teaching approach (Saleh, 2012c) and brain-based teaching methods (Saleh & Subramaniam, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%